2018
DOI: 10.4066/biomedicalresearch.29-17-867
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil of Coffee arabica L. husks: a brilliant source of antimicrobial and antioxidant agents

Abstract: The aim of present research work was to explore the constituents of the coffee husks oil obtained from Coffee arabica. L (Rubiaceae). Hydrodistillation extraction has been applied to extraction of volatile oil from coffee husks of C. arabica and the chemical constituents of the oil has been investigated by using by Gas Chromatography (GC), Gas Chromatography/Mass Spectrometry (GC/MS) and carban-13 Nuclear Magnetic Resonance ( 13 C NMR). GC and GC-MS analysis reveals the presence of fifty five components in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
1
19
0
5
Order By: Relevance
“…Hydro-distillation of C. arabia husks resulted in isolation of essential oil comprised of fifty five components, which were identified by GC-MS, as reported in our previous study and also the isolated oil have shown significant antibacterial and antioxidant activities [11]. As a continuation of our research [11] on the base of biological screening of obtained essential oil, the present study describes the QS and biofilm inhibitory properties (BI) of coffee husks oil against pathogenic bacteria using the reporter Chromobacterium violaceum CVO26. The coffee husks oil inhibited growth against pathogens, 500 µg/ml for CV O26 and 800 µg/ml for PAO1.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…Hydro-distillation of C. arabia husks resulted in isolation of essential oil comprised of fifty five components, which were identified by GC-MS, as reported in our previous study and also the isolated oil have shown significant antibacterial and antioxidant activities [11]. As a continuation of our research [11] on the base of biological screening of obtained essential oil, the present study describes the QS and biofilm inhibitory properties (BI) of coffee husks oil against pathogenic bacteria using the reporter Chromobacterium violaceum CVO26. The coffee husks oil inhibited growth against pathogens, 500 µg/ml for CV O26 and 800 µg/ml for PAO1.…”
Section: Resultssupporting
confidence: 54%
“…Air-dried husks (100 g) obtained from C. arabica were subjected to hydrodistallation for 3-4 h using an all glass Clevenger-type apparatus as described by Al-Yousef et al [11], to obtain essential oil 0.31% v/w. A total of 55 components were analysed in the essential oil and were identified on the basis of GC retention time and comparing with Wiley library 2006 as well as comparison the fragmentation patterns of their mass spectra with those reported in the literatures [11,15,16] and various of the identified components were identified as sesquiterpenes, amides, phenolic, fatty acids, sterols, alkanes furanol, compounds and alcohols [11].…”
Section: Essential Oil Isolation Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The agar well diffusion method was described in detail by Al-Yousef (2018). Detection of minimum inhibitory concentration (MIC) of ONP&ONP-PE toward some of drug resistant clinical strains was detected by broth dilution method, using p-iodonitro tetrazolium violet dye as an indicator of bacterial growth as described by Al-Yousef and Musarat (2018).…”
Section: Methodsmentioning
confidence: 99%